The Effect of Green Accounting Implementation and Profitability on Deferred Tax Assets in Property and Real Estate Companies (2023–2024) - Inke Br Sinuhaji; Joan Yuliana Hutapea; Harlyn L. Siagian (Sean Institute, 2026)
This study investigates the relationship between green accounting, profitability, and deferred tax assets (DTA) in property and real estate companies listed on the Indonesia Stock Exchange during the 2023–2024 period. The objective is to determine whether environmental accounting practices and financial performance influence the recognition of deferred tax assets. A quantitative approach is employed using secondary data derived from published financial statements, with multiple linear regression applied to test both partial and simultaneous effects of the independent variables on DTA. The results reveal that green accounting does not have a statistically significant effect on DTA, as indicated by a significance value of 0.605 and a beta coefficient of 0.247. Similarly, profitability, proxied by Return on Assets (ROA), shows no significant effect, with a significance value of 0.105 and a beta coefficient of 0.012. Simultaneous testing further confirms that both variables do not significantly explain variations in DTA, reflected in an F-value of 1.402 and a significance level of 0.249. In conclusion, the findings suggest that deferred tax asset recognition is primarily driven by fiscal factors, such as temporary differences and tax loss carryforwards, rather than by green accounting practices or profitability levels.